1982
DOI: 10.1159/000123408
|View full text |Cite
|
Sign up to set email alerts
|

Common Hypothalamic Sites for Activation of Sexual Receptivity in Female Rats by LHRH, PGE<sub>2</sub> and Progesterone

Abstract: Intrahypothalamic infusion of luteinizing hormone-releasing hormone (LHRH) facilitated lordosis responding in ovariectomized rats primed with estrogen (s.c.) and tested with male rats. A high degree of correlation exists in the hypothalamic sites responding to LHRH and estradiol or progesterone. Prostaglandin E2 was highly effective in inducing sexual behavior in rats not only at sites that yielded lordosis to LHRH, but also at sites unresponsive to LHRH. Our results suggest a common region of action in the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Also, no significant changes in adrenocortical secretion of cortisol and progesterone occurred after LHRH adminis tration; an important consideration because adrenocortical hormones may influence proceptivity in this primate [16], Female marmosets are highly receptive to the males' sexual advances both throughout their ovarian cycle [14] and after ovariectomy [16], It is therefore not surprising that changes in receptivity were not detected after LHRH treat ment. In the rat, LHRH potentiates receptivity by acting upon the hypothalamus [10,21,25], mid-brain central gray [23,26,27] and spinal cord [30], Application of an anti-LHRH globulin directly to the mid-brain central gray dis rupts lordosis [8,27], and research using LHRH analogues indicates that the behavioural potency of such peptides is to some extent distinct from their effects on luteinizing hor mone (LH) secretion [13,27,32], Primates also have exten sive LHRH containing neural networks in the brain [1-3, 19, 29], but whether these play a role in mediating the changes in proceptivity observed in the present study re main to be shown. Equally the question as to whether LHRH release normally potentiates proceptivity around the time of ovulation in the marmoset remains unanswered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, no significant changes in adrenocortical secretion of cortisol and progesterone occurred after LHRH adminis tration; an important consideration because adrenocortical hormones may influence proceptivity in this primate [16], Female marmosets are highly receptive to the males' sexual advances both throughout their ovarian cycle [14] and after ovariectomy [16], It is therefore not surprising that changes in receptivity were not detected after LHRH treat ment. In the rat, LHRH potentiates receptivity by acting upon the hypothalamus [10,21,25], mid-brain central gray [23,26,27] and spinal cord [30], Application of an anti-LHRH globulin directly to the mid-brain central gray dis rupts lordosis [8,27], and research using LHRH analogues indicates that the behavioural potency of such peptides is to some extent distinct from their effects on luteinizing hor mone (LH) secretion [13,27,32], Primates also have exten sive LHRH containing neural networks in the brain [1-3, 19, 29], but whether these play a role in mediating the changes in proceptivity observed in the present study re main to be shown. Equally the question as to whether LHRH release normally potentiates proceptivity around the time of ovulation in the marmoset remains unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioural effect of this treatment is therefore likely to have been mediated via a direct central action rather than indirectly through stimulating adrenocortical steroid secretion. These results provide the first demonstration that LHRH can potentiate the proceptive behaviour of a female primate.Luteinizing hormone releasing hormone (LHRH) ad ministered either peripherally [21,23] or centrally [10,20,[24][25][26][27]30] potentiates the lordosis reflex of oestrogenprimed rodents. Also hypogonadal LHRH-deficient mice do not show lordosis unless treated with oestrogen and LHRH [31].…”
mentioning
confidence: 99%
“…Blocking GPR30 action in these neurons using an siRNA reduced both the estradiol dendrimer conjugate- and 17β-estradiol-induced calcium oscillations, while the pure ER antagonist, ICI 182780, had no effect [59]. Since LHRH facilitates lordosis when infused into the medial preoptic area [60] or the VMH [61], it is possible that GPR30 activates lordosis behavior via stimulation of LHRH release. …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in animals in which vaginal stimulation or mating inhibit female sexual receptivity, prostaglandins are inhibitory (green anole lizard: Tokarz & Crews, 1981;garter snake: Whittier & Crews, 1986;guinea-pig: Marrone et ai, 1979). The behavioural responses appear to be induced by a direct action in the brain (Stacey & Peter, 1979;Diakow & Raimondi, 1981;Rodriguez-Sierra & Komisaruk, 1982). Injection of PGF-2a into non-pregnant sows induces the main elements of nest building, a major maternal behaviour (Blackshaw & Blackshaw, 1982).…”
Section: Discussionmentioning
confidence: 99%